From Selection to Success: Assessing the Impact of Student Admissions Strategies on the Quality of Education - Sugandi, Sugandi; Kulkarni, Shirin; Mulyana, Asep; Haedari, Amin; Casta, Casta (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study aims to evaluate the implementation of the new student admission program at one of the Madrasahs in Cirebon, focusing on the effectiveness of the selection system and its impact on the quality of students accepted. This study uses the Context, Input, Process, and Product (CIPP) evaluation model, providing a comprehensive framework for assessing the new student admission program. Data were collected through structured and unstructured interviews, observation, and documentation. Data analysis was carried out through reduction, presentation, and conclusion. The study results indicate that although the new student admission has succeeded in increasing the number of student registrations, the selection is still more focused on quantity than quality. This program is based on the vision of the madrasah, which is to develop students who are religious, intelligent, independent, and have good morals. Still, the selection process has not included in-depth academic and psychological evaluations. Although the infrastructure and socialization of the program are adequate, the quality of students accepted varies, affecting academic standards. This study suggests improvements in the selection process by implementing a more comprehensive assessment of student academic competence and character to improve student quality per the goals of madrasah education.